The impact of personalised therapies on respiratory medicine - J. Stuart Elborn (European Respiratory Review, 2013)
Stratified approaches to treating disease are very attractive, as efficacy is maximised by identifying responders using a companion diagnostic or by careful phenotyping. This approach will spare non-responders form potential side-effects. This has been pioneered in oncology where single genes or gene signatures indicate tumours that will respond to specific chemotherapies. Stratified approaches to the treatment of asthma with biological therapies are currently being extensively studied. In cystic fibrosis (CF), therapies have been developed that are targeted at specific functional classes of mutations. Ivacaftor, the first of such therapies, potentiates dysfunctional cystic fibrosis transmembrane conductance regulator (CFTR) protein Class III mutations and is now available in the USA and some European countries. Pivotal studies in patients with a G551D mutation, the most common Class III mutation, have demonstrated significant improvements in clinically important outcomes such as spirometry and exacerbations. Sweat chloride was significantly reduced demonstrating a functional effect on the dysfunctional CFTR protein produced by the G551D mutation. Symptom scores are also greatly improved to a level that indicates that this is a transformational treatment for many patients. This stratified approach to the development of therapies based on the functional class of the mutations in CF is likely to lead to new drugs or combinations that will correct the basic defect in many patients with CF.